2013
DOI: 10.4103/2249-4847.119995
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of iron status and red cell parameters in healthy full term small for gestational age neonates at birth

Abstract: Background:Hematological values of the newborn babies vary according to the gestational age and intrauterine growth.Objective:The objective of this study is to compare the iron status and red cell parameters in healthy term small for gestational age (SGA) and appropriate for gestational age (AGA) neonates.Materials and Methods:A prospective hospital based study was conducted in a tertiary care teaching institution of central India. 50 AGA and 50 SGA neonates were included in the study and serum iron, serum fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
1
4
0
1
Order By: Relevance
“… 8 , 9 Red blood cell (RBC) count is one of the erythrocyte parameters, and a very limited number of studies have reported that it can be used as a screening index or a treatment effect predictor of certain diseases. 10 , 11 One report has suggested the relation of elevated red cell distribution width with advanced liver fibrosis in nonalcoholic fatty liver disease. 12 Unfortunately, no report has connected the alteration of RBC count with human cancers, and the relation between reduced RBC count and poor liver function has never been investigated.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 Red blood cell (RBC) count is one of the erythrocyte parameters, and a very limited number of studies have reported that it can be used as a screening index or a treatment effect predictor of certain diseases. 10 , 11 One report has suggested the relation of elevated red cell distribution width with advanced liver fibrosis in nonalcoholic fatty liver disease. 12 Unfortunately, no report has connected the alteration of RBC count with human cancers, and the relation between reduced RBC count and poor liver function has never been investigated.…”
Section: Introductionmentioning
confidence: 99%
“… Serum iron over the neonatal period. (A) Full-term neonates: α shows the weighted mean (95% CI) for all studies seen in Supplemental Figure 3A; β, δ, and η show Prentice et al ( 99 ); χ shows Patidar et al ( 108 ); ε shows Balogh et al ( 94 ); ϕ shows Szabó et al ( 109 ); γ shows Andersson et al ( 103 ); ι shows Milman et al ( 39 ); φ shows Tsuzuki et al ( 110 ); κ shows Tiker et al ( 111 ); λ shows Yapakçı et al ( 112 ); μ shows Ozkiraz et al ( 113 ); ν shows Yamada and Leone ( 105 ). (B) Preterm neonates: α shows the weighted mean (95% CI) for all studies seen in Supplemental Figure 3B; β shows Lackmann et al ( 106 ); χ and δ show Tiker et al ( 111 ); ε shows Tsuzuki et al ( 110 ); ϕ shows Schiza et al ( 114 ); γ shows Yapakçı et al ( 112 ); η shows Celik et al ( 107 ); ι shows Yamada and Leone ( 105 ).…”
Section: Discussionmentioning
confidence: 99%
“…The burden of SGA infants in India is high with nearly 47% of neonates being SGA [ 19 ]. Because of low iron stores at birth; these neonates are at increased risk of developing iron deficiency and anemia later [ 8 , 9 ]. DCC is a well-established strategy to decrease the burden of iron deficiency anemia in infancy.…”
Section: Discussionmentioning
confidence: 99%
“…Small for gestational age (SGA) infants are those with birth weight less than 10th centile for the gestation and sex. Studies have shown that these infants have low iron stores at birth and are at risk of developing iron deficiency later [ 8 , 9 ]. This is due to placental vascular insufficiency mediated impairment in iron transport and increased utilization of iron to meet chronic hypoxia induced erythropoiesis.…”
Section: Introductionmentioning
confidence: 99%